The Species Identification in Traditional Herbal Patent Medicine, Wuhu San, Based on Shotgun Metabarcoding - Liu, Jinxin; Mu, Weishan; Shi, Mengmeng; Zhao, Qing; Kong, Weijun; Xie, Hongbo; Shi, Linchun (Frontiers in Pharmacology, 2021)
Traditional herbal patent medicine typically consists of multiple ingredients, making it challenging to supervise contamination by impurities and the improper use of raw materials. This study employed shotgun metabarcoding for the species identification of biological ingredients in traditional herbal patent medicine, Wuhu San. The five prescribed herbal materials found in Wuhu San were collected, and their reference sequences were obtained by traditional DNA barcoding using Sanger sequencing. Two lab-made and three commercial Wuhu San samples were collected, and a total of 37.14 Gb of shotgun sequencing data was obtained for these five samples using the Illumina sequencing platform. A total of 1 421 013 paired-end reads were enriched for the Internal Transcribed Spacer 2 (ITS2), psbA and trnH intergenic spacer region (psbA-trnH), maturase k (matK), and ribulose-1, 5-bisphosphate carboxylase (rbcL) regions. Furthermore, 80, 11, 9, and 8 operational taxonomic units (OTUs) were obtained for the ITS2, psbA-trnH, matK, and rbcL regions, respectively, after metagenomic assembly, annotation, and chimeric detection. In the two lab-made mock samples, all labeled ingredients in the Wuhu San prescription were successfully detected, and the positive control, Panax quinquefolius L., was detected in the HSZY172 mock sample. Three species, namely Angelica sinensis (Oliv.) Diels, Saposhnikovia divaricata (Turcz. ex Ledeb.) Schischk., and Carthamus tinctorius L., belonging to three labeled ingredients, Angelicae Sinensis Radix (Danggui), Saposhnikoviae Radix (Fangfeng), and Carthami Flos (Honghua), were detected in the three commercial samples. Angelica dahurica (Hoffm.) Benth.& Hook. f. ex Franch.& Sav., the original Angelicae Dahuricae Radix (Baizhi) species, was only detected in WHS003. Arisaema erubescens (Wall.) Schott, Arisaema heterophyllum Blume, or Arisaema amurense Maxim., the original Arisaematis Rhizoma (Tiannanxing) species, were not detected in any of the commercial samples, which could be attributed to the fact that this medicinal material underwent extensive processing. In addition, the Saposhnikovia divaricata adulterant was detected in all the commercial samples, while 24 fungal genera, including Aspergillus, were identified in both the lab-made and commercial samples. This study showed that shotgun metabarcoding provided alternative strategy and technical means for identifying prescribed ingredients in traditional herbal patent medicine and displayed the potential to effectively complement traditional methods.